2011
DOI: 10.1007/s00415-011-6293-5
|View full text |Cite
|
Sign up to set email alerts
|

Observational clinical study in juvenile-adult glycogenosis type 2 patients undergoing enzyme replacement therapy for up to 4 years

Abstract: The objective of this study was to describe a large Italian cohort of patients with late-onset glycogen storage disease type 2 (GSDII) at various stages of disease progression and to evaluate the clinical effectiveness of alglucosidase alpha enzyme replacement therapy (ERT). Previous studies showed in late-onset patients ERT efficacy against placebo and variable response in uncontrolled studies. Seventy-four juvenile or adult GSDII patients were treated with ERT in a multicenter open label, non-randomized stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 11 publications
7
102
1
4
Order By: Relevance
“…While a study by van der Ploeg (2010) included walking and nonventilated patients [6], the patients included in this retrospective observational study had a wide spread of disease spectrum including severely affected patients that required NIV (9/22) or were confined to wheelchairs (3/22) [17,19]. This more severely afflicted cohort necessitated careful clinical assessment measures and it was not always possible to get all the relevant tests performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While a study by van der Ploeg (2010) included walking and nonventilated patients [6], the patients included in this retrospective observational study had a wide spread of disease spectrum including severely affected patients that required NIV (9/22) or were confined to wheelchairs (3/22) [17,19]. This more severely afflicted cohort necessitated careful clinical assessment measures and it was not always possible to get all the relevant tests performed.…”
Section: Discussionmentioning
confidence: 99%
“…ERT maintained efficacy for 2 years [5] that resulted in stabilization of VCmax following ERT for 3 years and longer in LOPD patients [16,17,18]. There are additional reports showing significant improvement in pulmonary function, preventing or delaying ventilator dependency and prolonging survival [6,18,[19][20][21][22][23][24]25] and led to fewer hospital admissions [24]. ERT also demonstrated improvements in muscle strength, pulmonary function and survival [15].They reported less fatigue and improvement in motor function and quality of life to a variable extent [6,19,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A limited number of ERT trials and observational studies have been published on late-onset patients (van der Ploeg 2010; Strothotte et al 2010;Angelini et al 2012;Regnery et al 2012). An observational study (Deroma et al 2014) in eight juvenile GSDII cases reported marked decrease of CK after ERT and stabilisation of disease course.…”
Section: Discussionmentioning
confidence: 99%